2016
DOI: 10.1016/j.ultsonch.2015.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characteristics and sonocatalytic activities of calcined γ-Fe2O3 and TiO2 nanotubes/γ-Fe2O3 magnetic catalysts in the degradation of Orange G

Abstract: In this work, γ-Fe2O3 and TiO2 NTs/γ-Fe2O3 composites with good magnetism and sonocatalytic activity were prepared by a facile polyol method and utilize the principle of isoelectric point method, respectively. The structural and magnetic features of the prepared calcined γ-Fe2O3 and composite catalysts were investigated by transmission electron microscopy (TEM), powder X-ray diffraction (XRD), surface analysis, UV-Vis diffuse reflectance spectra (UV-Vis DRS), vibrating sample magnetometry (VSM) and zeta potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(17 citation statements)
references
References 47 publications
2
13
0
2
Order By: Relevance
“…), etc. have been successfully coupled with various photocatalysts to induce magnetic behaviour in the composite material and allow easy magnetic separation [39,[77][78][79]. Since the photocatalyst remains powdery upon incorporation of the magnetic nanoparticles, this does not compromise its surface area and the distribution of the photocatalyst in the aquatic medium.…”
Section: Introductionmentioning
confidence: 99%
“…), etc. have been successfully coupled with various photocatalysts to induce magnetic behaviour in the composite material and allow easy magnetic separation [39,[77][78][79]. Since the photocatalyst remains powdery upon incorporation of the magnetic nanoparticles, this does not compromise its surface area and the distribution of the photocatalyst in the aquatic medium.…”
Section: Introductionmentioning
confidence: 99%
“…As the pore aperture is relatively wide in the range of 5-10 nm, it suggested that the proportion of mesoporous volume to the total aperture is in greater proportion, mesopore structure is one of the most reasons for large surface area. 37 In contrast, the BET and pore-size distribution of the nonporous nanoparticles is displayed in Fig. 7b.…”
Section: Composition and Microstructurementioning
confidence: 92%
“…Using this equation, the band gap energy of these composites can be obtained by 2 against the band gap energies can be estimated from the intercept of the straight line fitted from the liner part of the graphics to the axis of the abscissa (Fig. 2(b) [9,10], it may be due to the effect of composite formation. It is possible properties could be generated by interaction of the materials.…”
Section: Methodsmentioning
confidence: 99%